Police Efforts in Tackling Environmental Crimes Due to Illegal Gold Mining - Marlonsius Simbolon; Fitriati; Bisma Putra Pratama (Master of Law Program, Ekasakti University, 2025)
Illegal gold mining in Manggani, Nagari Koto Tinggi, Fifty Cities Regency, causes serious environmental damage as well as a source of livelihood for the community, so that the countermeasures face ecological and socio-economic dilemmas. This study aims to analyze the role and obstacles of the 50 City Police Satintelkam in overcoming environmental crimes due to illegal gold mining through cross-police cooperation, especially with the Pasaman Police. This research is a legal research with descriptive-analytical specifications using a normative juridical approach supported by empirical data; Secondary data is obtained through literature studies, while primary data is collected through interviews, then analyzed qualitatively. The results of the study show that Satintelkam plays a strategic role in early detection, mapping of actors and networks of cross-regional miners, collecting and disseminating intelligence information, and mobilizing cross-agency cooperation for unlicensed mining control operations. Cross-police cooperation expands the scope of supervision and enables enforcement of illegal gold distribution channels and financiers outside the administrative area of the 50 City Police. However, the effectiveness of countermeasures is constrained by limited human resources and monitoring technology in protected forest areas, the support of some communities for mining as an economic source, indications of collusion between individuals and mining companies, and coordination between institutions that are not optimal. It is recommended to strengthen the capacity of police intelligence, increase sustainable multi-sector coordination, and legal education to the public to realize more effective and equitable enforcement of environmental laws.